Kontribusi Media Sosial dalam Meningkatkan Partisipasi Politik Generasi Muda di Indonesia - Muhammad Mughni Labib; Syafril Maulidan Zidqi; Amrish Yahya; Aurellia Keshena Arsifa (Idarotuna : Journal of Administrative Science, 2026)
In this rapidly evolving digital era, social media has emerged as one of the most powerful tools for influencing public opinion, disseminating political knowledge, and encouraging youth engagement in the democratic process. This study examines how social media helps young people in Indonesia become more informed, engaged, and politically participatory. Various sources, including related books, research reports, internet articles, and scientific journals, were analyzed as part of the desk research. According to various studies, social media has two functions: as an effective tool for political education and as a platform for young people to express themselves politically. On the other hand, social media platforms can give rise to problems such as the spread of hoaxes, political division, and a fast-paced information culture. This study demonstrates that critical awareness and digital literacy are crucial for young people to use social media effectively to uphold democratic values.